MicroRNA-4417 is a tumor suppressor and prognostic biomarker for triple-negative breast cancer - Wong, Chen Khuan (Cancer Biol Ther, 2019)
Triple-negative breast cancer (TNBC) is the most aggressive form of breast cancer with poor prognosis due to lack of druggable targets such as hormone and growth factor receptors. Therefore, identification of targetable regulators such as miRNAs could provide new avenues for therapeutic applications. Here, we report that the expression of miR-4417 is suppressed during the progression of TNBC cells from non-malignant to the malignant stage. MiR-4417 is localized to chromosome 1p36, a region with high frequency of loss of heterozygosity in multiple cancers, and its biogenesis is DICER-dependent. Low expression of miR-4417 is significantly associated with worse prognosis in TNBC patients, while overexpression of miR-4417 is sufficient to inhibit migration and mammosphere formation of TNBC cells in vitro. Overall, our findings suggest miR-4417 exerts a tumor suppressive effect and thereby could serve as a prognostic biomarker and therapeutic tool against TNBC.